Genome-Wide Analyses of the Genetic Screening of C2H2-Type Zinc Finger Transcription Factors and Abiotic and Biotic Stress Responses in Tomato (Solanum lycopersicum) Based on RNA-Seq Data - Zhao, Tingting; Wu, Tairu; Zhang, Jia; Wang, Ziyu; Pei, Tong; Yang, Huanhuan; Li, Jingfu; Xu, Xiangyang (Frontiers in Genetics, 2020)
C2H2-type zinc finger proteins are classic and extensively studied members of the zinc finger family. C2H2-type zinc finger proteins participate in plant growth, development and stress responses. In this study, 99 C2H2-type zinc finger protein genes were identified and classified into four groups, and many functionally related cis-elements were identified. Differential C2H2-ZFP gene expression and specific responses were analyzed under drought, cold, salt, and pathogen stresses based on RNA-Seq data. Thirty-two C2H2 genes were identified in response to multiple stresses. Seven, 3, 5, and 8 genes were specifically expressed under drought, cold, salt, and pathogenic stresses, respectively. Five glycometabolism and sphingolipid-related pathways and the endocytosis pathway were enriched by KEGG analysis. The results of this study represent a foundation for further study of the function of C2H2-type zinc finger proteins and will provide us with genetic resources for stress tolerance breeding.